Reşat Ekrem Koçu's İstanbul Ansiklopedisi; or an obsessive collector's attempt to make his private narrative public - Ayvaz, Mehmet Emre. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2007., 2007)
This thesis is an interpretive study to analyse Resat Ekrem Koçu’s unfinished work Đstanbul Ansiklopedisi. The study attempts to reveal the relationship between the private narrative of the author and the collective narrative that he seeks to construct, with due emphasis on the implications of and meanings attached to the genre ‘encyclopedia.’ After the observation that a certain urge to ‘collect’ underlies Koçu’s encyclopedic project, the thesis concentrates upon the autobiographical quality inherent in the textual structure of Đstanbul Ansiklopedisi. Since the collecting activity implies the expression of one’s self through a meaningful arrangement of a group of objects, it is perhaps justifiable that the entries constituting Đstanbul Ansiklopedisi may also be construed as object-themes that serve as the means to construct an autobiographical narrative. A further suggestion of this study is that the intersection of the ‘impartiality’ of the genre of encyclopedia and the subjective content of the autobiographical narrative results in the articulation of a modern self. Finally, this study invites readers to see Đstanbul Ansiklopedisi as a transition from the private sphere of the collection to the public sphere of an encyclopedia. Through this transition, or metamorphosis, it is suggested, the articulation of a modern authorial voice is rendered possible.|Keywords: Encyclopedia, Collection, Autobiography, Self